Pemilihan Kepala/Wali Desa/Nagari Dengan Sistem E-Voting Di Kabupaten Agam Provinsi Sumatera Barat - Muhammad Irham; Miracle Soplanit (Faculty of Law, Universitas Pattimura, 2017)
Village head election must be continuously developed and adapted to the development of the community in the village. The Indonesian nation has stated clearly in the constitution of the 1945 Constitution of the Republic of Indonesia, the fourth paragraph which is the purpose of national and state life